Sustainable intensification of small-scale mariculture systems: Farm-level insights from the coastal regions of India - Parappurathu, Shinoj; Menon, Muktha; Jeeva, Charles; Belevendran, Johnson; Anirudhan, Anuraj; Lekshmi, P. S. Swathi; Ramachandran, C.; Padua, Shelton; Aswathy, Natarajan; Ghosh, Shubhadeep; Damodaran, Divu; Megarajan, Sekar; et al. (Frontiers in Sustainable Food Systems, 2023)
This study undertakes a comprehensive assessment of selected mariculture enterprises in the coastal regions of India, centered on long-term sustainability as the key focus. This is juxtaposed against India's ambitious blue economy targets and policy thrust that pin on the expansion of mariculture as a promising avenue for enhancing marine fish production. Farm-level, region-specific, techno-economic, and socio-cultural factors associated with, and conditional on, sustainable intensification of mariculture-based production systems are examined in detail. The Principles-Criteria-Indicators (PCI) approach is used to establish the linkage between identified farm-level indicators and various dimensions of sustainability. While the selected enterprises were assessed to be technically and economically viable in general, glaring gaps were evident on key indicators of sustainability such as the legitimacy of access over water bodies, use of quality seed and feed, institutional credit access, market access, and fair marketing practices, optimal stocking density, mechanization, use of renewable energy, adoption of environmental-friendly culture practices, farm surveillance, crew safety, and social protection. This indicates the need for taking proactive measures to ensure the long-term sustainability of mariculture, particularly in the initial stages of establishment when such interventions are easy to adopt. Based on the insights obtained from the analysis, a broad set of strategies, policy options, and institutional interventions critical to scaling-up coastal mariculture enterprises along the east and west coasts of India are presented.